Analisis Kinerja Keuangan KUD Werdhi Mendala Di Desa Batubulan Kecamatan Sukawati Kabupaten Gianyar - NI MADE WAHYUNINGSIH; I KETUT RANTAU; I DEWA AYU SRI YUDHARI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
The Financial Performance Analysis of Rural Cooperative of Werdhi MendalaIn Batubulan Village Sukawati Sub-District of Gianyar Regency KUD or rural cooperative is expected to be able to realize economic democracy in theefforts to develop cooperatives into an independent people's economic institutions. Thefinancial statements are an important tool for obtaining information related to thefinancial condition and results of cooperative activities. The objectives of the researchare to determine (1) the ability of KUD to fulfill its short term financial obligationassessed from the liquidity ratio, (2) how far is the KUD assets financed by its debtassessed from the solvency ratio, (3) how effective the KUD in using its funding sourceassessed from the activity ratio and (4) the ability of KUD to obtain the Return onInvestment assessed by the profitability ratio. Types of data used in the study arequalitative data and quantitative data with financial ratio analysis as a method of dataanalysis in the research. Data Sources of the study are primary and secondary data. Thekey informants were the Manager and Finance Department of KUD Werdhi Mendala.Data analysis method used is financial ratio analysis. Financial ratios used are the ratioof liquidity, solvency ratio, activity ratio and profitability ratio.The result of ratioanalysis during 2011-2015 shows that liquidity ratio at current ratio and quick ratio issaid to be very inadequate. The solvency ratio in total debt to equity ratio and total debtto total asset are said to be very inadequate. The ratio of activity to total assets turnoveris not good and receivable turnover is said to be very inadequate. Profitability ratio onnet profit margin is said to be quite capable, return of investment / ROI is said to be veryinadequate and return of equity / ROE (Rentability of Own Capital) is said to be quitecapable.